PROBLEM QUESTIONS OF ARTERIAL HYPERTENSION ACCORDING TO 10-YEARS INVESTIGATION - Нейко, Є. М.; Оринчак, М. А. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
During 2001-2010 years 3 scientific-research works were completed on the implementation of the National “Program of prevention and treatment of arterial hypertension in Ukraine". A number of specific risk factors and predictors of cardiovascular events were found in hypertensives with metabolic syndrome – obesity/overweight in 100%, heredity in 55%, hypodynamia in 60%, dyslipidemia in 75%, hyperinsulinemia in 60%, smoking in 50% among man. Different approaches to combined treatment were grounded for the hypertensives with metabolic syndrome, taking into account the level of insulin in blood. When hyperinsulinemia is present an adequate control of blood pressure is achieved in 60-70% cases if applying 2-3 component antihypertensive therapy with including angiotensin converting enzyme inhibitors (enalapril/ramipril) and angiotensin II receptor blocker (telmisartan/irbesartan) in combination with diuretics (indapamide/torasemid) and calcium antagonist (lerkamen/felodipin) or beta-blocker (nebivolol) and statins (atorvastatin/simvastatin).